Pengaruh Tax Avoidance Dan Profitabilitas Terhadap Nilai Perusahaan Dengan Good Corporate Governance Sebagai Variabel Moderasi - Novia Sukmandari; Saiful Anwar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine and prove the effect of tax avoidance and profitability with the moderating variable of good corporate governance on firm value. Manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020 are the population of this study. A sample of 20 companies was optained using purposive sampling technique. WrapPLS 7.0 for windows is used as a tool in the Structural Equation Model (SEM) analysis method in this study. This study optained result stating that there was no effect of tax avoidance o firms value. Meanwhile, it was found that firm value was positively influence by profitability. Good corporate governance cannot provide a moderating effect on the relationship between tax avoidance and firm value, but good corporate governance provides a moderating effect and strengthens the relationship between profitability and firm value. Keywords : Tax Avoidance; Profitability; Firm Value; Good Corporate Governance